Pengaruh Kualitas Pelayanan, Fasilitas, dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan : Studi pada Bengkel Yamaha Kondang Motor Simo Boyolali - Ema Handayani; Listyowati Puji Rahayu; Donna Setiawati (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Indonesia's economic growth in recent years has encouraged the development of various industries and businesses. Consequently, companies must adapt to market changes while maintaining service quality to build customer loyalty. In the service industry, customer satisfaction and loyalty are key indicators of business success. The automotive service sector, including motorcycle workshops, is one such industry. Customer loyalty is influenced by service quality, facilities, and customer satisfaction. This study examines the effect of service quality, facilities, and customer satisfaction on customer loyalty at Yamaha Kondang Motor Simo Workshop in Boyolali. The research was motivated by field observations showing a mismatch between the limited number of technicians and the increasing number of customers, as well as inconsistencies in findings from previous studies regarding the relationships among these variables. This research employed a descriptive quantitative approach. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling. The data were analyzed using statistical techniques to describe the research object and examine the relationships among the variables. The results indicate that service quality has a positive and significant effect on customer loyalty. Facilities also have a significant effect on customer loyalty, while customer satisfaction positively and significantly influences customer loyalty. Furthermore, service quality, facilities, and customer satisfaction simultaneously have a significant effect on customer loyalty at Yamaha Kondang Motor Simo Workshop, Boyolali.